Caixa de correio: lugar de entrada, de passagem e de acúmulo de memórias - Tania de Castro Araujo (2016)
The mailbox, an antique object, is still present in our daily lives, despite being little used for the traditional personal and affective correspondences. Its function has been replaced by the virtual and electronic communication, made possible by the imminence of contemporary technological devices. The mailbox as a place of entrance, transit and accumulation of memories, is, in this essay, the nucleus of the motif around which are examined the connections between the art world and questionings regarding the fields of politics, writing and the female world from the mid-twentieth century. The photographic record of their presence in the urban architecture of the city of Belo Horizonte2 translates the inspiring poetic face of the course of this investigation, which seeks to emphasize the movement of Postal Art / Mail Art, contextualizing it, both nationally and globally, in the political and artistic arena, highlighting the intense production, involvement and activeness of Pernambuco based artist Paulo Bruscky.